Access, Universal Design and the Sustainability of Teaching Practices: a Powerful Synchronicity of Concepts at a Crucial Conjuncture for Higher Education - Fovet, Frederic (Indonesian Journal of Disability Studies, 2017)
Sustainability in Higher Education is usually interpreted as a concept applying solely to operations management and energy policy. Though the applicability of the concept to social justice is immediately tangible, few campuses have found organic and pragmatic ways to extend principles of sustainability to their equity, diversity or inclusion practices, or to convince their community of the need to do so. This study examines the unique experience of North American campus having attempted this progressive osmosis between the two concepts. Access has represented the opportunity for this rethink. As individual, retroactive accommodations become increasingly obsolete when it comes to providing access to learning to large number of students with specific needs entering post-secondary education, sustainability has become an increasingly appealing lens with which to devise a new framework for inclusion seeking systemic change in pedagogical practices. The campus in question implemented a proactive drive for the implementation of Universal Design for Learning from 2011 and this paper presents the analysis of the various and complex ways access and sustainability have become entwined in campus policies. The outcomes are particularly relevant for the Global South in that it may encourage Higher Education institutions in developing countries to avoid the temporary appeal of medical model based measures of inclusion and the precedents set in the Global North over the last two decades, and to focus instead on social model based policies that seek the development of sustainable and inclusive teaching practices from the onset.